Measuring Key Factors in E-Government Participation: A Rasch Modeling Approach with Human Resource Management Considerations - Askolani, Askolani; Sari, Maya; Gautama, Budhi Pamungkas; Perdana, Yoga; Maulid, Dibias Lazuardi (Jurnal Manajemen Pelayanan Publik, 2019)
This study examines the subject matter of e-government participation among Indonesian citizens, aiming to assess its effectiveness in enhancing government-citizen relationships through social media and good governance practices. The objectives include constructing and validating a survey instrument based on 15 experience items related to e-government perception, utilizing Rasch modeling to analyze data from 101 respondents. Results indicate strong reliability (Cronbach's Alpha = 0.94) and significant correlations (Person raw score-to-measure correlation = 0.99), affirming the instrument's capability to measure variables influencing e-government participation effectively. The findings align well with Rasch model expectations (Infit and Outfit MNSQ within acceptable ranges), highlighting the instrument's suitability for comprehensive assessment. In conclusion, this research contributes insights into enhancing government transparency, accountability, and responsiveness, crucial for fostering trust and effective governance in the digital era.